Prevalence of menstrual dysfunction in Norwegian long-distance runners participating in the Oslo Marathon games - Tomten, S. E. (Scandinavian Journal of Medicine & Science in Sports, 1996)
The objective of this study was to estimate the prevalence of athletic amenorrhea in a wide range of long-distance runners and the relation to possible risk factors. The study group consisted of 187 long-distance runners between 16 and 46 years of age. Information was obtained through a mailed questionnaire consisting of 32 different entries, including questions on age, leanness, training history, menstrual history, performance level, stress, as well as some sociological and nutritional aspects. Seventy-six per cent of the responding runners had normal menstrual function, 9.5% had minor irregularities (O), and 14.6% were amenorrheic (A), which is defined as absence of menstrual bleeding for more than 3 consecutive months the previous year. Half of the amenorrheic group had not had menstrual bleeding at all that year. The runners with menstrual disorders (O + A) had a significantly higher incidence of stress fractures. The most important factors associated with menstrual disorders were a feeling of conflict associated with food; age; and the age of menarche. There was no evidence that age of menarche was associated with an early training debut per se, the frequency and intensity of prepubertal training was not taken into account. All subgroups (E, O, and A) had low body mass index scores, and body composition did not seem to vary with menstrual status within the study group. Thus a high prevalence of menstrual disorders was observed in Norwegian long-distance runners, a condition associated with increased training loads, but even more with age, menarchal age and a feeling of nutritional conflict.